Pelatihan Bahasa Inggris Komunikatif Dalam Meningkatkan Pendapatan Bagi Staff Prama Sanur Beach Hotel - Ni Wayan Kasni; Dewa Ayu Kadek Claria; Ni Luh Anik Puspa Ningsih (Linguistic Community Services Journal, 2025)
English language training is an effort to improve staff knowledge and strategic management, thereby increasing Prama Sanur Beach Hotel's revenue. Survey results from previous trainings indicate that staff's ability to actively communicate using English functions, such as offering, refusing, handling complaints, apologizing, and explaining, still lacks standard structures and appropriate lexical choices. The training will be implemented by prioritizing several language functions related to offering, handling complaints, refusing, apologizing, and describing. The increased human resource capabilities are expected to increase the number of tourist visits, which will also impact hotel revenue. The post-test results from the training indicate that Prama staff, particularly front office staff, food and beverage service, and marketing staff, are already able to use English functions well.